2015
DOI: 10.1016/j.ijfoodmicro.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cell immobilization on the growth dynamics of Salmonella Typhimurium and Escherichia coli at suboptimal temperatures

Abstract: Predictive microbiology has recently acknowledged the impact of the solid(like) food structure on microbial behavior. The presence of this solid(like) structure causes microorganisms to grow as colonies and no longer planktonically as in liquid. In this paper, the growth dynamics of Salmonella Typhimurium and Escherichia coli were studied as a function of temperature, considering different growth morphologies, i.e., (i) planktonic cells, (ii) immersed colonies and (iii) surface colonies. For all three growth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 45 publications
4
31
1
1
Order By: Relevance
“…However, in this study, L. monocytogenes growth between the two systems was similar, neglecting the influence of the growth morphology. Similar microbial dynamics in liquids and on aqueous gels have also been observed in literature (Smet et al, 2015). Nevertheless, growth parameters will be discussed one by one.…”
Section: Monocytogenes Growth In Liquids Versus Aqueous Gels (Critsupporting
confidence: 72%
See 4 more Smart Citations
“…However, in this study, L. monocytogenes growth between the two systems was similar, neglecting the influence of the growth morphology. Similar microbial dynamics in liquids and on aqueous gels have also been observed in literature (Smet et al, 2015). Nevertheless, growth parameters will be discussed one by one.…”
Section: Monocytogenes Growth In Liquids Versus Aqueous Gels (Critsupporting
confidence: 72%
“…This observation indicates that stressing temperature favours planktonic microbial growth, although at more optimal temperature levels microbial growth on solid surfaces is more favourable, as also reported in Smet et al (2015). It has been reported that μ max in liquid systems is higher than μ max on solid surfaces Meldrum et al, 2003;Theys et al, 2008).…”
Section: Accepted Manuscriptsupporting
confidence: 71%
See 3 more Smart Citations